Narrating juvenile mental disorders in Calixthe Beyala’s selected novels (2014)
Critics of Calixthe Beyala’s feminist discourse have located her narratives within the walls of radical feminism. For instance, her feminist language is often labelled with linguistic violence. Beyala’s outcry against oppression is Voiced through adolescent girls who she refers to as femme-fillette and whose gloomy world is characterised by parental violence. The social and psychological degradation of the children Beyala presents in her novels are instances of immeasurable misery impregnated with aggression of adults towards children. Through these same children, Beyala impugns various forms of disintegration eating into postcolonial Africa. Introducing a psychological paradigm into the readings and interpretations of Beyala’s radical feminist works using Freudian psychoanalytic approach to literary criticism and Nietsche’s theory of resentment clearly shows that Beyala is a feminist author whose anger is directed towards male hegemony, and it forms the avenue through which she aptly portrays that young girls living under oppression decline into psychological wrecks.